Pulmonary interstitial emphysema requiring lobectomy. Complications of assisted ventilation. Issue 5 (May 1978) - Drew, J H; Landau, L I; Acton, C M; Kent, M; Campbell, P E
Abstract : An infant with hyaline membrane disease treated with intermittent positive pressure ventilation developed pulmonary interstitial emphysema localised to one lobe after collapse of the affected lobe. The development of tension and further symptoms necessitated lobectomy, after which the infant became totally asymptomatic. Microscopy of the resected lobe showed the unusual feature of giant cells lining the air-containing cysts. The presence of these multinucleate cells suggested the cysts may have represented greatly dilated lymphatic channels resulting from rupture of gases into the pulmonary lymphatics.